El nuevo régimen de la litispendencia en el Reglamento Bruselas I bis y el reto afrontado por la jurisdicción china (Revista Electrónica de Estudios Internacionales, 2025)
The new regime of lis pendens in Regulation Brussels I bis has extended its application to the third states including China. This may be a challenge to Chinese jurisdiction since it has not established a uniform criterion to deal with lis pendens. However, the provisions regarding the relation with third states in the new regime of lis pendens still need further examination. Besides, the unilateral statement in the Regulation may be unfair from the Chinese perspective. In this way, it may be relevant for the Chinese and the EU legislators to seek a solution through the establishment of a bilateral Convention that is specialized at dealing with the regime of lis pendens.